2022
DOI: 10.1155/2022/9461377
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Analysis of Regional Economy Development on Local Environmental Protection and Natural Resources Utilization from the Perspective of Big Data

Abstract: The ecological restoration and civilization construction is one of the key tasks in China. The economic development of different regions has different effects on the resource protection and utilization. In the face of complex natural conditions and resource-rich areas, how to carry out the ecological environment promotion work is put forward. The urbanization level of the Yangtze River region increases from 17.9% to 60.6%, showing the characteristics of rapid expansion. In the face of urban diseases such as un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This analysis underscores the importance of developing robust data protection mechanisms that are capable of addressing the unique challenges posed by environmental Big Data, including the need for effective validation and distribution practices that do not compromise data security. Wen (2022) examines the impact of regional economic development on local environmental protection and natural resources utilization from the perspective of Big Data. The study emphasizes the role of digital technology in driving local economic development while ensuring efficient resource utilization and promoting high-quality, common economic development.…”
Section: Key Developments In Protecting Sensitive Environmental Datamentioning
confidence: 99%
“…This analysis underscores the importance of developing robust data protection mechanisms that are capable of addressing the unique challenges posed by environmental Big Data, including the need for effective validation and distribution practices that do not compromise data security. Wen (2022) examines the impact of regional economic development on local environmental protection and natural resources utilization from the perspective of Big Data. The study emphasizes the role of digital technology in driving local economic development while ensuring efficient resource utilization and promoting high-quality, common economic development.…”
Section: Key Developments In Protecting Sensitive Environmental Datamentioning
confidence: 99%
“…Liu et al (2022) found that digitalization, represented by Internet of things and other digital technologies, is the primary driver of inclusive green growth in cities. Considering ecological priority, 43% of China's population benefited from the development of digital technology in 2019 (Wen, 2022). Besides, big data can be used to guide green building development, new products, green building materials, and new materials, to implement cleaner production, and to prevent pollution (Fang, 2018).…”
Section: Green Economic Developmentmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%